REVITALIZING KHULUQ IN Q.S. LUQMAN: QUR’ANIC–PROPHETIC CHARACTER EDUCATION IN THE DIGITAL ERA - Indana, Lina; Taubah, Mufatihatut (International Journal of Educatio Elementaria and Psychologia, 2025)
Character education is essential for developing individuals with integrity and strong moral character. Nevertheless, contemporary educational institutions face serious challenges, including moral decline, the weakening of social ethics, and rapid changes driven by the socio-digital environment. The Qur’an and the Hadith serve as comprehensive sources of ethical guidance, particularly through the educational teachings of Luqman al-Hakim as presented in Surah Luqman. This study aims to analyze five core character values derived from Q.S. Luqman verses 12–19, namely faith (tawhid), gratitude, filial piety (birr al-walidayn), patience, and enjoining good and forbidding evil (amr ma‘ruf nahy munkar). In addition, the study proposes relevant strategies for implementing these values among Indonesian students in the contemporary era. The research adopts a descriptive–analytical literature review approach, employing hermeneutic analysis and content analysis of primary and secondary sources. The findings indicate that these five values represent fundamental dimensions of Islamic character education. Their effective implementation requires a process of spiritual transformation (takhalli–tajalli–tajalli), adaptive integration within the curriculum, structured habituation in daily educational practices, and the strengthening of teachers’ roles as moral exemplars (uswah hasanah). Overall, this study contributes by offering a model for internalizing Islamic character values and supporting the revitalization of moral education within Islamic educational institutions.